2021
DOI: 10.1186/s40517-021-00188-x
|View full text |Cite
|
Sign up to set email alerts
|

An online survey to explore the awareness and acceptance of geothermal energy among an educated segment of the population in five European and American countries

Abstract: Advances in new technologies and the desire to achieve a sustainable and safe energy supply, enable communities to transition from conventional to renewable resources, such as geothermal energy. Perception and acceptance amongst different audiences have a high impact on the feasibility of energy projects, which is an important aspect to analyze. For this reason, this study focuses on describing the level of awareness and acceptance of deep geothermal energy within an educated segment of the population in five … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Global experience indicates that government support is key to geothermal development through loan programs, industrial insurance, grants, and exploration projects [96]. In addition, Balzan-Alzate et al [97] indicated that the acceptance and knowledge of this type of energy must be considered in the energy contexts of each country because the change in context could alter the objectives in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Global experience indicates that government support is key to geothermal development through loan programs, industrial insurance, grants, and exploration projects [96]. In addition, Balzan-Alzate et al [97] indicated that the acceptance and knowledge of this type of energy must be considered in the energy contexts of each country because the change in context could alter the objectives in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Frequently, users' acceptance analyses are carried out by means of dedicated interviews or surveys [29]. If extended surveys are submitted within a broad context, researchers can achieve representative and generalizable results [30,31]. For instance, regarding the social acceptance of transitions towards local energy communities, Azarova et al [32] showed that in European countries such as Italy and Switzerland, a key role is played by national and regional political support.…”
Section: The Role Of Media In Fostering Energy Transitionmentioning
confidence: 99%
“…Renewable energy is becoming increasingly recognized as an effective tool for addressing climate change [18][19][20][21]. Therefore, public opinion studies on energy issues have revealed strong support with different degrees for REs [22][23][24][25], and polarized views about non-renewables including coal, nuclear energy, natural gas, and oil [26][27][28][29]. Most studies assessing public acceptance of renewable energy sources have been conducted in fossil fuel importing countries or countries with highly diversified economies [24,[30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…However, the opposition to geothermal energy in comparison with oil, coal, and nuclear power implies that most unknowledgeable individuals have limited or no knowledge about this renewable resource. Indeed, according to a study conducted in five European and American countries where geothermal energy has been already exploited, this source was widely accepted particularly by the educated sectors of the population [23]. Despite the fact that bioenergy and geothermal energy systems still have a significantly lower impact on the environment than fossil fuels [73], no technology is without adverse environmental effects.…”
mentioning
confidence: 99%